Psychophysiological methods and criteria for the selection of individual metered loads in athletes of taekwondo section - G. V. Ohromiy; N.U. Makarova; A.M. Kasyuha (Physical Education of Students)
Purpose: scientific rationale approaches Express-diagnostics for athletes of taekwondo section by psychophysiological parameters. Material: Total surveyed 84 people, including 68 boys and 16 girls. Were defined backup capabilities, exercise tolerance and selection of adequate individual dose of loads in preparation for the international competition, participants - taekwondo athletes. Was attended by representatives of Ukraine, Russia and Lithuania. Age groups of participants: 6 - 16 years. Athletes have different levels and different schools of training. Results: evaluation of exercise tolerance and definition of an adequate level of motor mode in taekwondo athletes in terms of the difference of lability (DL) before and after training, revealed: high and very high nervous system (NS) lability. These figures correspond to high and very high tolerance to physical loads. The respondents who had difference of liability (DL) <0, were well-trained athletes and their high points of strength of nervous system testified about good backup capabilities (withstand great and continuous loads). In 78 % of the tested load was chosen adequately. Less than 20% of the respondents noted the average backup capabilities. They need individual correction dose loads to increase adaptive capacity. Insignificant 10%, the share of respondents had low exercise tolerance at the average values NS strength, which indicates a good backup capabilities. The direct dependence: respondents with high levels on state of health, activity and mood - low levels of anxiety, frustration, aggression and rigidity. Conclusions The proposed optimized approach Express-diagnostics according to psychophysiological parameters allow you to determine the level of physical endurance, speed adaptation athletes in the sections taekwondo and adequate response to the loads.